Peningkatan Hasil Belajar Mata Pelajaran Pengantar Pariwisata dengan Tema Lokasi Wisata Dalam dan Luar Negeri Dengan Metode Pemanfaatan Media Video di Kelas 10 Tata Boga 1 Semester Ganjil Tahun Pelajaran 2019/2022. - Misna Liharni (Transformasi Manageria: Journal of Islamic Education Management, 2022)
The ineffectiveness of teaching by the teacher is thought to be due to the teacher's lack of accuracy in using learning media. This is marked by the tendency of teachers to teach the material using the classical lecture method. One of the public schools that has sufficient introductory tourism value. This is because the teaching implementation system that is carried out is less effective, so that in the implementation of introductory tourism teaching that is carried out it is necessary to conduct research in order to obtain the most effective teaching to be used both on current and future opportunities online. Based on the results of the research that has been carried out, the researcher found that the students of class X Catering 1 were still low at 47.2% of the results in accordance with the KKM that had been set. To improve student learning outcomes Introduction to tourism, the action taken is to apply a learning model with the video method. Keywords: Improving Learning Outcomes, Tourism, Video Media.